Synthesis and in vitro anticancer activity of 6-chloro-7-methyl-5H-[1, 3, 4]thiadiazolo[3, 2-a]pyrimidin-5-one derivatives: molecular docking and interaction with bovine serum albumin. Issue 4 (4th July 2018) - Gaonkar, Supreet; Sunagar, Manjunath G.; Deshapande, Narahari; Belavagi, Ningaraddi S.; Joshi, Shrinivas D; Dixit, Sheshagiri R; Khazi, Imtiyaz Ahmed M.
ABSTRACT: A novel series of 6-chloro-7-methyl-5 H -[1, 3, 4]thiadiazolo[3, 2- a ]pyrimidin-5-one derivatives were synthesized. Structure of the newly synthesized compounds was established by their analytical and spectroscopic data. The title compounds were evaluated for their anticancer activity against human breast cancer (T-47D) and lung cancer (NCI-H226) cell lines. Effects of compounds on the cell morphology of these cell lines were studied. Among the series of compounds tested, 6-chloro-7-methyl-2-(4-((2-(piperidin-1-yl)ethylamino)methyl) phenyl)-[1, 3, 4]thiadiazolo[3, 2- a ]pyrimidin-5-one [MTDP4(9)] exhibited good anticancer activity against both cell lines. Further, the binding interaction of [MTDP4(9)] with bovine serum albumin has been investigated by UV, fluorescence and molecular docking studies.